2021
DOI: 10.4314/jasem.v25i4.11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pH of Drilling Fluid Produced from Local Clay and Additives

Abstract: Maintaining the pH of drilling fluid with suitable additives is one of the important operation for efficient drilling operations.  However, commercial hydroxides are mostly used to control the pH of the drilling fluid. This paper evaluates locally sourced pH additives of burnt plantain heads (BPH), burnt ripe burnt ripe plantain peels (BRPP), and burnt banana plantain peels (BBPP) in comparison with conventional potassium hydroxide (KOH) and sodium hydroxide (NaOH) as suitable agents to control pH of drilling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The pH determination provides the free ions concentration H⁺ (or OH − ). Drilling sludge is generally basic and its pH may vary from 8 to 10 depending on the case [44]. It was found that:…”
Section: Effect Of the Aging Time On The Ph Of Different Hpam Suspens...mentioning
confidence: 99%
“…The pH determination provides the free ions concentration H⁺ (or OH − ). Drilling sludge is generally basic and its pH may vary from 8 to 10 depending on the case [44]. It was found that:…”
Section: Effect Of the Aging Time On The Ph Of Different Hpam Suspens...mentioning
confidence: 99%